Peningkatan Keterampilan Menulis Teks Biografi Dengan Model Pembelajaran Think Pair Share Pada Kelas X TKJ 1 di SMK Negeri 1 Percut Sei Tuan - Oktaviani Napitupulu (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this class action research is to improve the skills of writing biographical texts with a Think Pair Share model in class X network and computer engineering one (X TKJ 1) at SMK Negeri 1 Percut Sei Tuan. The background of this research is the low skills of writing biographical texts in the class X network and computer engineering one (X TKJ 1). This research method uses a qualitative descriptive method. The classroom action research (CAR) process uses planning, action, and reflection steps. The data analysis used was a comparative descriptive technique and data collection used tests and observations. Based on the results of data analysis and observations made which consisted of 2 cycles and each cycle was divided into 2 face-to-face meetings as follows. In cycle I students get an average score of 71.74, that value (has not reached) Minimum Completeness Criteria (75) and continued in cycle II with an average score of 84.11 with a total of 28 students out of 35 students. The conclusion is that the learning outcomes of the learning model with the Think Pair Share model in learning biographical texts can improve students' skills in writing logically and creatively.